Full-scale process modification on anaerobic-aerobic treatment of industrial wastewater - He, Guanghui. (2008)
In this study, two process modifications to the plant were examined. In the phase I study, four wasterwater streams of low COD concentration but readily degradable wasterwater from different chemical manufacturing plants were channeled into the two-stage biological treatment plant, serving as the dilute water.